Assessing the Impact of Competency and Intellectual Capital on MSMEs' Performance: Insights from Banjarmasin City - Mardah, Siti; Harnida, Muthia; Santi, Apriya; Fathurrohman, Fathurrohman; Pratiwi.A, Nida (International Journal of Science, Technology & Management, 2025)
This research examines the impact of competency and intellectual capital on the performance of micro, small, and medium-sized enterprises (MSMEs) in Banjarmasin City. This research used a quantitative approach. Data were collected via an online questionnaire with 51 MSME actors as respondents. Data were analyzed using multiple linear regression methods. The results indicate that intellectual capital, encompassing knowledge, expertise, and innovation, significantly influences performance. However, competency does not show a significant impact on MSMEs’ performance. These findings provide insight into the condition of MSMEs in Banjarmasin City and can provide additional empirical evidence on the effect of intellectual capital. Additionally, this result can serve as a reference for policymakers to help MSMEs improve their performance through targeted training, mentorship, and collaborative networks. The implications of this research emphasize the importance of developing intellectual capital for MSMEs to enhance their performance. The finding that competency has an insignificant impact on performance warrants further investigation. Additionally, this result can serve as a reference for policymakers to help MSMEs improve their performance through targeted training, mentorship, and collaborative networks. The implications of this research emphasize the importance of developing intellectual capital for MSMEs to enhance their performance. The finding that competency has an insignificant impact on performance warrants further investigation. Keywords: Competency, Intellectual Capital, MSMEs, Performance. Resource-based view